Magnetic Hyperthermia–Synergistic H2O2 Self‐Sufficient Catalytic Suppression of Osteosarcoma with Enhanced Bone‐Regeneration Bioactivity by 3D‐Printing Composite Scaffolds. (4th November 2019) - Dong, Shaojie; Chen, Yu; Yu, Luodan; Lin, Kaili; Wang, Xudong
Abstract: Chemotherapy resistance and bone defects caused by surgical excision of osteosarcoma have been formidable challenges for clinical treatment. Although recently developed nanocatalysts based on Fenton‐like reactions for catalytic therapy demonstrate high potential to eliminate chemotherapeutic‐insensitive tumors, insufficient concentration of intrinsic hydrogen peroxide (H2 O2 ) and low intratumoral penetrability hinder their applications and therapeutic efficiency. The synchronous enriching intratumor H2 O2 amount or nanoagents and promoting osteogenesis are intriguing strategies to solve the dilemma in osteosarcoma therapy. Herein, a multifunctional "all‐in‐one" biomaterial platform is constructed by co‐loading calcium peroxide (CaO2 ) and iron oxide (Fe3 O4 ) nanoparticles into a three‐dimensional (3D) printing akermanite scaffold (AKT‐Fe3 O4 ‐CaO2 ). The loaded CaO2 nanoparticles act as H2 O2 sources to achieve H2 O2 self‐sufficient nanocatalytic osteosarcoma therapy as catalyzed by coloaded Fe3 O4 nanoagents, as well as provide calcium ion (Ca 2+ ) pools to enhance bone regeneration. The synergistic osteosarcoma‐therapeutic effect is achieved from both magnetic hyperthermia as‐enabled by Fe3 O4 nanoparticles under alternative magnetic fields and hyperthermia‐enhanced Fenton‐like nanocatalytic reaction for producing highly toxic hydroxyl radicals. Importantly, the constructed 3D AKT‐Fe3 O4 ‐CaO2 composite scaffolds are featured with favorable bone‐regeneration activity, providing a worthy base and positive enlightenment for future osteosarcoma treatment with bone defects by the multifunctional biomaterial platforms. Abstract : A multifunctional "all‐in‐one" biomaterial platform is constructed to achieve H2 O2 self‐sufficient nanocatalytic osteosarcoma therapy and provide calcium ion (Ca 2+ ) pools to enhance bone regeneration. In particular, a synergistic osteosarcoma‐therapeutic effect is achieved from both magnetic hyperthermia and the hyperthermia‐enhanced Fenton‐like nanocatalytic reaction. Importantly, the constructed 3D composite scaffolds are featured with favorable bone‐regeneration activity as demonstrated both in vitro and in vivo.